Pharmaceutical Drug Separations by HPCE: Practical Guidelines - Mc Laughlin, G. M.; Nolan, J. A.; Lindahl, J. L.; Palmieri, R. H.; Anderson, K. W.; Morris, S. C.; Morrison, J. A.; Bronzert, T. J. (Journal of liquid chromatography, 1992)
As governmental regulations become more encompassing and restrictive, it has become more important to develop high efficiency separation methods for pharmaceutical drugs. High Performance Capillary Electrophoresis (HPCE) is becoming accepted as a primary and complementary (with HPLC) separation technique. Researchers that have not previously used HPCE may not be familiar with the myriad of parameters that can be manipulated to achieve the desired efficiency, selectivity, or resolution. The purpose of this work is to develop some practical advice, guidelines, and limitations of HPCE in the separation of pharmaceutical drugs. Several classes of pharmaceutical drugs are used to illustrate the physical and buffer parameters that can be manipulated. Some important physical parameters are discussed. Free solution concepts are illustrated using pH control, ionic strength, ion pairing reagents, and organic modifiers. Examples illustrate Micellar Electrokinetic Capillary Chromatography (MECC)-a tool for the separation of charged and uncharged species. The final major area of discussion is the separation of chiral drugs, where HPCE shows great promise. Use of cyclodextrins (natural/substituted, varying ring sizes, other buffer additives, etc.) is the primary focus. Understanding the manipulative capabilities of these parameters offers almost unlimited potential in the separation of pharmaceutical drugs.